Structural dynamism of chiral sodium peraza-macrocycle complexes derived from cyclic peptoids. Issue 34 (16th August 2021) - Schettini, Rosaria; D'Amato, Assunta; Araszczuk, Alicja Malgorzata; Della Sala, Giorgio; Costabile, Chiara; D'Ursi, Anna Maria; Grimaldi, Manuela; Izzo, Irene; De Riccardis, Francesco
Abstract : Peraza-macrocycles are the most studied chelating agents. An efficient approach toward chiral cyclen and hexacyclen ligands, starting from cyclic peptoids, is described. Abstract : A variety of cyclen and hexacyclen derivatives decorated with ( S )-1-phenylethyl side chains or ( S )-pyrrolidine units have been prepared via a reductive approach from the corresponding cyclic peptoids containing N -( S )-(1-phenylethyl)glycine and l -proline residues. Spectroscopic and DFT studies on their Na + complexes show that point chirality and ring size play a crucial role in controlling the structural dynamism of 1, 2-diaminoethylene units and pendant arms. The detection of highly symmetric C 4 - and C 3 -symmetric metalated species demonstrates that a full understanding of the relationship between the structure and conformational properties of peraza-macrocyclic metal complexes is possible.